The effects of different iron and phosphorus treatments on the formation and morphology of iron plaque in rice roots (Oryza sativa L) - Hu, Haoran; Bi, Liyan; Wang, Lei; Zhan, Fangdong; Liang, Xinran; Qin, Li; Li, Yuan (Frontiers in Plant Science, 2024)
Introduction: Rice (Oryza sativa L.) is a pivotal cereal crop worldwide. It relies heavily on the presence of iron plaque on its root surfaces for optimal growth and enhanced stress resistance across diverse environmental conditions.To study the crystallographic aspects of iron plaque formation on rice roots, the concentrations of Fe 2+ and PO4 3-were controlled in this study. The effects of these treatments were assessed through comprehensive analyses encompassing root growth status, root surface iron concentration, root vitality, enzyme activities, and microstructural characteristics using advanced techniques such as root analysis, scanning electron microscopy (SEM), and ultrathin section transmission electron microscopy (TEM).The results demonstrated that an increase in the Fe 2+ concentration or a decrease in the PO4 3-concentration in the nutrient solution led to improvements in various root growth indicators. There was an elevation in the DCB (dithionite-citrate-bicarbonate) iron content within the roots, enhanced root vitality, and a significant increase in the activities of the superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) enzymes. Moreover, as the Fe 2+ concentration increased, amorphous iron oxide minerals on the root surface were gradually transformed into ferrihydrite particles with sizes of approximately 200 nm and goethite particles with sizes of approximately 5 μm. This study showed that an increase in the Fe 2+ concentration and a decrease in the PO4 3-concentration led to the formation of substantial iron plaque on the root surfaces. It is noteworthy that there was a distinct gap ranging from 0.5 to 3 μm between the iron plaque formed through PO4 3-treatment and the cellular layer of the root surface.Discussion: This study elucidated the impacts of Fe 2+ and PO4 3-treatments on the formation, structure, and morphology of the iron plaque while discerning variations in the spatial proximity between the iron plaque and root surface under different treatment conditions.